Minute Ventilation During Hypoxia is Augmented with Capsaicin Supplementation in Aged Mice - Receno, Candace N. (Respir Physiol Neurobiol, 2019)
Capsaicin is an agonist for transient receptor potential vanilloid 1 (TRPV1), and acute injection results in an increased frequency and tidal volume in young rats. It is unknown how capsaicin influences breathing in aged mice. We tested the hypothesis that capsaicin supplementation would elicit an augmented pattern of breathing in old mice compared to controls. Male 22-month old C57BL/6J mice consumed a diet containing capsaicin (50 ppm) or lecithin control for one month. Breathing patterns were obtained prior to/following the dietary supplementation period using unrestrained barometric plethysmography. Frequency, tidal volume (VT), minute ventilation (VE), VE to expelled carbon dioxide ratio (VE/VCO(2)) and VT divided by inspiratory time (VT/T(i)) were analyzed at baseline and during a 15-minute hypoxic exposure (10% O(2)). Capsaicin supplemented mice showed greater VE, VE/VCO(2) and TV/T(i) during hypoxic exposure compared to controls, with no change at baseline. Overall, these findings suggest an acute augmented response to hypoxia following capsaicin administration in older mice.